MODEL TUKAR BELAJAR (LEARNING EXCHANGE) BERBASIS KULIAH KERJA NYATA USAHA (KKU) - Enceng Mulyana (Jurnal Ilmiah Visi, 2006)
Topic covers how KKU program is being developed in universities. Its objective is to build up the spirits of entrepreneurships and independency among higher education students who are majoring in NFE. The learning exchange model is basically applied. It makes use of adult education principles. Through the model, students who are in the program of KKU are expected to share their knowledge and skills with entrepreneurs. In return, the entrepreneurs would exchange with their experiences in doing the business so that they become resource persons. Somehow, instead of sharing and exchanging knowledge, skills and experiences, students and entrepreneur just tend to socialize and communicate ini the activity. A conceptual model of learning exchange is needed so that the process of learning is intensively progressive and productive in developing cognitve and affective domains.